2008
DOI: 10.1002/app.27580
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the elasticity and permeability of vulcanized films made with skim and cream natural rubber latex

Abstract: The purpose of this study was to gain a clearer picture of the structure and properties of vulcanized films made with skim and cream latex from Hevea brasiliensis. The two properties targeted for this study were the elasticity of the films and their permeability to acetone. Surface characterization by atomic force microscopy revealed that vulcanization substantially modified the structure of the films compared to unvulcanized films. Unlike unvulcanized films, particle identity was retained in the vulcanized fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In contrast, the particle contours of non-crosslinked skim particles disappeared, resulting in blurred spots. 20 The result also agreed with the internal morphology of prevulcanised latex particles examined by the phase transfer/bulk polymerisation/TEM technique which revealed the uniform crosslink structure of SPVS particles. 7 Analysis of CHD-PMA Nanocapsules.…”
Section: Resultssupporting
confidence: 79%
“…In contrast, the particle contours of non-crosslinked skim particles disappeared, resulting in blurred spots. 20 The result also agreed with the internal morphology of prevulcanised latex particles examined by the phase transfer/bulk polymerisation/TEM technique which revealed the uniform crosslink structure of SPVS particles. 7 Analysis of CHD-PMA Nanocapsules.…”
Section: Resultssupporting
confidence: 79%
“…Finally, rubber molecules from neighboring RPs are crosslinked (inter‐particle crosslinked network) by residual curing agents at high temperature known as post‐vulcanization process, where eventually all the RPs lost their identities and coalesced into a continuous film. However, it was previously reported that the vulcanization structure mostly occurred during pre‐vulcanization followed by the post‐vulcanization in film‐forming period . For example, in concentrated NR (CNR) latex film, the morphology of the RPs was dependent upon the level of crosslinking in that the RP identity was retained over long aging periods for highly crosslinked particles, creating rough surface .…”
Section: Introductionmentioning
confidence: 99%
“…However, it was previously reported that the vulcanization structure mostly occurred during pre‐vulcanization followed by the post‐vulcanization in film‐forming period . For example, in concentrated NR (CNR) latex film, the morphology of the RPs was dependent upon the level of crosslinking in that the RP identity was retained over long aging periods for highly crosslinked particles, creating rough surface . On the other hand, pre‐vulcanized latex film surface made from skim NR latex was smooth and contours of RPs were no longer discernible, leading to greater elasticity than that of the CNR latex film .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations